P-NE005. Correlation between nerve conduction study and vibration perception threshold in dental residents. Issue 8 (August 2021) - Limbu, Rekha; Thakur, Dilip; Limbu, Nirmala; Parajuli, Prakash; Agrawal, Navin; Sharma, Shivalal; Maskey, Robin
Abstract : Introduction. Dentists are exposed to handheld vibrating tools in their daily clinical practice. Repetitive exposure to vibration has been shown to cause peripheral nerve dysfunction. Nerve conduction study (NCS) provides objective assessment of peripheral nerve function. Vibration perception threshold (VPT) measures the sensorineural abnormalities in the distal fingers associated with vibration. Most studies have been performed in symptomatic subjects. Therefore, we aimed to study correlation between vibration perception threshold and NCS in apparently healthy asymptomatic dental residents. Methods. This cross-sectional study enrolled 22 apparently healthy asymptomatic dental residents exposed to vibrating hand-held tools at least for 10 months (exposure group) and 22 age-matched medical residents who were not exposed to vibration (non-exposure group). They were selected by purposive sampling method. VPT was measured on the palmar surface of second and fifth fingertips of both hands. NCS of the bilateral median and ulnar nerves were recorded by belly-tendon montage. Pearson's correlation was applied to find out the relation between NCV and VPT. A p-value of < 0.05 was considered significant. Results. Positive correlations were found between right median nerve proximal latency and VPT on left hand; minimum F-wave latency of left median nerve and VPT on left hand and minimum F-wave latency of left ulnar nerve and VPT on left hand. Conclusion. Significant correlations were observed between VPT and electrophysiological parameters indicating that both methods are valuable for evaluating peripheral nerve dysfunction.